DAMPAK PANDEMI COVID-19 TERHADAP PENINGKATAN RESIKO KEMISKINAN DI INDONESIA - Sugeng Setyadi; Lili Indriyani (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2021)
The Covid-19 pandemic is estimated to be able to cause a global recession, this will have a tremendous impact disrupting economic activities to prevent the virus from being carried out, so that it can affect people's income. This study aims to see whether Covid-19 can increase the risk of poverty in Indonesia. This study uses a number of factors that affect the incidence of poverty due to COVID-19 in 34 provinces of Indonesia in 2020, using multiple regression research methods. The results showed that the variable number of positive cases of COVID-19 had a positive and significant effect on poverty. Life expectancy and inequality have a positive but insignificant effect on poverty and GDP per capita has a negative but significant effect on poverty. Based on the regression results, each increase in the number of positive cases of COVID-19 by 1 person will increase the number of poverty by 0.0087 people. Every year increase in life expectancy will increase the number of poverty by 130,11932 people. Every increase in income inequality by 1% will increase the number of poverty by 533,7175 people. Each increase in PDRB per capita is Rp. 1000 then will reduce the number of poverty by 0.0234 people. Keywords: COVID-19, Poverty, Life Expectancy, Gini Ratio and PDRB per Capita